On the existence of holomorphic foliations on Hopf manifolds - Beltran, Andrés (2024)
In this paper, we investigate the problem of the existence of holomorphic foliations on 3-dimensional Hopf manifolds, with a particular focus on exceptional type manifolds. Hopf manifolds, being compact, non-Kähler complex manifolds, provide a fertile ground for the analysis of non-trivial phenomena in the study of holomorphic foliations. In particular, these manifolds exhibit geometric structures that allow for the emergence of complex dynamical behaviors, making them a case of special interest.